PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN SATUAN KERJA LINGKUP PEMBAYARAN KPPN METRO - Elmira Febri Darmayanti (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
The purpose of this study is to investigate the possibility of cause and effect by observing and searching for causal factors through data and knowing whether the Competencies of Human Resources, Accounting Information Systems, Internal Control Systems partially and simultaneously affect the Quality of Financial Statements. The research used was quantitative research. This research was conducted using primary data. Respondents are 93 people came from 3 (three) areas of the KPPN Metro payment unit, namely East Lampung, Central Lampung, Metro City. Based on the results of the study, it was found that partially the Human Resource Competency variable had a significant positive effect on the Quality of Financial Reports, the Accounting Information System variable had a positive effect on the Quality of Financial Reports, while the variable that the Internal Control System had a significant negative effect on the Quality of Financial Statements. The Human Resource Competency, Accounting Information System, and Internal Control System variables simultaneously influence the Quality of Financial Statements.